Dietary Supplementation With Lactobacillus plantarum Ameliorates Compromise of Growth Performance by Modulating Short-Chain Fatty Acids and Intestinal Dysbiosis in Broilers Under Clostridium perfringens Challenge - Wang, Baikui; Zhou, Yuanhao; Mao, Yulong; Gong, Li; Li, Xiang; Xu, Shujie; Wang, Fei; Guo, Qianpeng; Zhang, Huihua; Li, Weifen (Frontiers in Nutrition, 2021)
Abstract: Clostridium perfringens is an important zoonotic pathogen associated with food contamination and poisoning, gas gangrene, necrotizing enterocolitis or necrotic enteritis in humans and animals. Dysbacteriosis is supposedly associated with the development of C. perfringens infection induced necrotic enteritis, but the detailed relationship between intestinal health, microbiome and C. perfringens infection induced necrotic enteritis remains poorly understood. This research investigated the effect of probiotics on the growth performance and intestinal health of broilers, and the involved roles of intestinal microbiota and microbial metabolic functions under C. perfringens infection. Results showed that sub-clinical necrotic enteritis was successfully induced as evidenced by the significant lower body weight (BW), supressed feed conversion ratio (FCR), decreased ileal villus height and mucosal barrier function, increased ileal histopathological score and bursal weight index. Lactobacillus plantarum or Paenibacillus polymyxa significantly attenuated C. perfringens induced compromise of growth performance (BW, FCR) and ileal mucosa damage as illustrated by the increased ileal villus height and villus/crypt ratio, the decreased ileal histopathological score and the enhanced ileal mucosal barrier function. L. plantarum also significantly alleviated C. perfringens-induced enlarged bursa of fabricius and the decreased levels of ileal total SCFAs, acetate, lactate and butyrate. Furthermore, dietary L. plantarum improved C. perfringens infection induced intestinal dysbiosis as evidenced by significantly enriched short-chain fatty acids-producing bacteria (Lachnospiraceae, Ruminococcaceae, Oscillospira, Faecalibacterium, Blautia), reduced drug-resistant bacteria (Bacteroides, Alistipes) and enteric pathogens (Escherichia coli, Bacteroides fragilis) and bacterial metabolic dysfunctions as illustrated by significantly increased bacterial fatty acid biosynthesis, decreased bacterial lipopolysaccharide biosynthesis and antibiotic biosynthesis (streptomycin and vancomycin). Additionally, the BW and intestinal SCFAs were the principal factors affecting the bacterial communities and microbial metabolic functions. The above findings indicate that dietary with L. plantarum attenuates C. perfringens induced compromise of growth performance and intestinal dysbiosis by increasing SCFAs and improving intestinal health in broilers.